Geopolitics, Rural Development and Transformation in Mranak Village, Demak Regency - Pugara, Ade (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Kenneth Lynch (2005) wrote that the rural area is an area which has particular characteristics such as agriculture activity is a basic sector in the economy, has natural resources either renewable or unrenewable and most of the people take farmer as their livelihood. The changes of rural elementâ€™s condition are usually called as rural transformation or regional transformation. Usually, the rural transformation came from the effect of rural development, however not at all. As long is known that development canâ€™t be separated with the political preference of people and political condition. The research of â€œgeopolitics, rural development and rural transformationâ€ wants to identify the influence of geopolitics aspects to rural development and transformation. This research conduct with qualitative method particularly deductive qualitative positivism. The output of the study is the models regarding the influences of geopolitics aspects to rural development and transformation. Trough mathematic logical system â€œif a is b and if b is c, when if the input is a so the result is câ€, the researcher can find not only the influence of the geopolitics (aspects) to rural development and transformation but also the reliability of relationship between them although using qualitative methods.